Glass fiber yarn and its manufacturing method

The introduction of tungsten sulfide-coated inorganic particles into the glass fiber yarn manufacturing process addresses the issue of yarn tearing during spinning, resulting in improved slipperiness and thermal stability.

JP7659675B1Active Publication Date: 2025-04-09NANYA PLASTICS CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024022741
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-12-27
Filing Date
2024-02-19
Publication Date
2025-04-09
Estimated Expiration
2044-02-19

AI Technical Summary

Technical Problem

Existing glass fiber yarns are prone to tearing during the spinning process due to lack of slipperiness.

Method used

A glass fiber yarn is developed by forming a tungsten sulfide gel, heat-treating it to form a tungsten sulfide powder, and coating this powder onto inorganic particles, which are then mixed with glass raw materials and spun into yarns.

Benefits of technology

The resulting glass fiber yarns exhibit improved slipperiness and reduced tearing during spinning, with a maximum coefficient of static friction ranging from 0.39 to 0.48, and enhanced thermal stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007659675000001_ABST
    Figure 0007659675000001_ABST
Patent Text Reader

Abstract

To provide a glass fiber yarn capable of effectively preventing the glass fiber yarn from easily breaking during spinning, and a manufacturing method thereof. [Solution] The method includes the steps of dissolving a tungsten compound in a first organic solution to form a tungsten compound gel, adding a sulfur source to the tungsten compound gel and stirring the sulfur source and the tungsten compound gel to form a tungsten sulfide gel, maintaining the tungsten sulfide gel in an environment of 600°C to 1200°C for 4 to 6 hours to form a tungsten sulfide powder, coating the surfaces of a plurality of surface-modified inorganic particles with the tungsten sulfide powder to form modified inorganic particles, mixing a plurality of the modified inorganic particles into a molten glass raw material, and spinning the glass raw material containing the plurality of the modified inorganic particles to form a glass fiber yarn.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a fiberglass yarn and a method for producing the same, and more particularly to a fiberglass yarn containing tungsten sulfide and a method for producing the same. [Background technology]

[0002] In the existing methods for producing glass fiber yarns, the glass fiber yarns have insufficient lubricity, and therefore, there is a problem in that the glass fiber yarns easily break during the spinning process. Summary of the Invention [Problem to be solved by the invention]

[0003] The technical problem to be solved by the present invention is to provide a new glass fiber yarn and a manufacturing method thereof that can make up for the shortcomings of the existing technology, specifically, to provide a glass fiber yarn and a manufacturing method thereof that can effectively improve the problem of glass fiber yarn breakage during the spinning process. [Means for solving the problem]

[0004] In order to solve the above technical problems, one of the technical solutions adopted by the present invention includes a tungsten compound gel forming step of dissolving a tungsten compound in a first organic solution to form a tungsten compound gel; a tungsten sulfide gel forming step of adding a sulfur source to the tungsten compound gel and stirring the sulfur source and the tungsten compound gel to form a tungsten sulfide gel; a heat treatment step of maintaining the tungsten sulfide gel in an environment of 600°C to 1200°C for 4 to 6 hours to form a tungsten sulfide powder; and and a spinning step of spinning the glass raw material containing the surface-modified inorganic particles to form a plurality of glass fiber yarns. The present invention relates to a method for manufacturing a glass fiber yarn, the method including: a coating step of coating a tungsten sulfide powder on the surfaces of a plurality of inorganic particles to form surface-modified inorganic particles, wherein the content of the tungsten sulfide powder is in the range of 0.01 wt% to 5 wt% relative to 100 wt% of the total weight of the surface-modified inorganic particles; a mixing step of mixing a plurality of the surface-modified inorganic particles with a molten glass raw material; and a spinning step of spinning the glass raw material containing the surface-modified inorganic particles to form a plurality of glass fiber yarns.

[0005] Preferably, after the tungsten sulfide gel-forming step and before the heat-treating step, the method for producing glass fiber yarn further includes a washing and drying step of washing and filtering the tungsten compound gel multiple times, and then calcining the tungsten compound gel.

[0006] Preferably, in the coating step, after dispersing the tungsten sulfide powder in the second organic solution, the tungsten sulfide powder and the second organic solution are added to the plurality of inorganic particles, and then the tungsten sulfide powder, the second organic solution and the plurality of inorganic particles are stirred, so that the tungsten sulfide powder is coated on the surface of the plurality of inorganic particles to form a plurality of surface-modified inorganic particles.

[0007] Preferably, the tungsten compound is tungsten hexachloride.

[0008] Preferably, the weight ratio of the tungsten compound to the sulfur source ranges from 5:1 to 8:1.

[0009] Preferably, the inorganic particles are at least one selected from the group consisting of silicon dioxide, titanium dioxide, aluminum hydroxide, magnesium hydroxide, calcium carbonate, aluminum oxide and calcined kaolin.

[0010] Preferably, the particle size of each of said inorganic particles ranges from 0.01 μm to 50 μm.

[0011] Preferably, the content of the surface-modified inorganic particles ranges from 0.1 wt % to 5 wt %, based on the total weight of all said glass fiber yarns being 100 wt %.

[0012] Preferably, each of said fiberglass yarns has a maximum static coefficient of friction in the range of 0.39 to 0.48.

[0013] In order to solve the above technical problems, another technical solution adopted by the present invention is to provide a glass fiber yarn comprising a glass frit and a plurality of surface-modified inorganic particles dispersed in the glass frit. Wherein, each of the surface-modified inorganic particles comprises an inorganic particle and a tungsten compound coated on the inorganic particle. In addition, the content of the tungsten sulfide powder ranges from 0.01wt% to 5wt% based on the total weight of all the surface-modified inorganic particles being 100wt%. The inorganic particles are at least one selected from the group consisting of silicon dioxide, titanium dioxide, aluminum hydroxide, magnesium hydroxide, calcium carbonate, aluminum oxide and calcined kaolin.

[0014] Preferably, the particle size of each of the inorganic particles is in the range of 0.01 μm to 50 μm, and the content of the surface-modified inorganic particles is in the range of 0.1 wt % to 5 wt % relative to the total weight of all the glass fiber yarns (100 wt %).

[0015] Preferably, the glass fiber yarn has a maximum static coefficient of friction in the range of 0.39 to 0.48.

[0016] One beneficial effect of the present invention is that the glass fiber yarn and the manufacturing method thereof provided by the present invention can effectively solve the problem that the existing glass fiber yarn easily breaks during the spinning process through the technical solution of "a tungsten compound gel forming step, a tungsten sulfide gel forming step, a heat treatment step, a coating step, a mixing step and a spinning step" and "a plurality of surface-modified inorganic particles are dispersed in the glass raw material".

[0017] In order to better understand the characteristics and technical contents of the present invention, please refer to the following detailed description and drawings of the present invention, which are merely illustrative of the present invention and do not limit the protection scope of the present invention. [Brief description of the drawings]

[0018] [Figure 1] 1 is a flowchart of a method for producing a glass fiber yarn in an embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram of a glass fiber yarn according to an embodiment of the present invention. [Diagram 3] FIG. 1 is a schematic diagram of a surface-modified inorganic particle according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] The following describes the embodiments disclosed in the present invention through specific examples of the "glass fiber yarn and its manufacturing method" according to the present application. Those skilled in the art can understand the advantages and effects of the present invention from the disclosure of this specification. The present invention can be implemented or applied in other different embodiments. Each detail in this specification can be modified and changed based on various aspects or applications without departing from the spirit of the present invention. In addition, the drawings of the present invention are for simple and schematic illustration only and do not show actual dimensions. In the following embodiments, the technical matters related to the present invention will be further described, but the disclosed contents do not limit the present invention. In addition, the term "or" used in this specification may include any one or more combinations of related items according to actual circumstances.

[0020] Throughout this specification, terms such as "first," "second," and "third" may be used to describe various components or signals, but it should be understood that these components and signals should not be limited by these terms. These terms are used primarily to distinguish one component from another or one signal from another. Furthermore, as used herein, the term "or" can include any one or combination of the associated listed items, where appropriate.

[0021] [Method of manufacturing glass fiber yarn] As shown in Figures 1 to 3, Figure 1 is a flow chart of a method for producing a glass fiber yarn in an embodiment of the present invention, Figure 2 is a schematic diagram of a glass fiber yarn in an embodiment of the present invention, and Figure 3 is a schematic diagram of a surface-modified inorganic particle in an embodiment of the present invention. The embodiment of the present invention provides a method for producing a glass fiber yarn, including a tungsten compound gel forming step S110, a tungsten sulfide gel forming step S120, a heat treatment step S130, a coating step S140, a mixing step S150, and a spinning step S160.

[0022] In the tungsten compound gel forming step S110, the tungsten compound is dissolved in a first organic solution to form a tungsten compound gel. In this embodiment, the tungsten compound is, for example, tungsten hexachloride, and the first organic solution is, for example, ethanol or isopropanol, but the present invention is not limited thereto. In the tungsten compound gel forming step, the tungsten compound and the first organic solution do not need to be stirred or heated.

[0023] In the tungsten sulfide gel forming step S120, a sulfur source is added to the tungsten compound gel, and the sulfur source and the tungsten compound gel are stirred to form a tungsten sulfide gel. The sulfur source can be, for example, sulfur powder or hydrogen sulfide gas.

[0024] When sulfur powder is used as the sulfur source, the weight ratio of the tungsten compound to the sulfur source is in the range of 5:1 to 8:1. The amount of the tungsten compound used is in the range of 400 to 800 weight units, and the amount of the sulfur source used is in the range of 75 to 115 weight units, but more preferably, the amount of the tungsten compound used is in the range of 500 to 700 weight units, and the amount of the sulfur source used is in the range of 85 to 105 weight units. More preferably, the amount of the tungsten compound used is about 600 weight units, and the amount of the sulfur source used is about 96.8 weight units. The weight ratio of the tungsten compound to the first organic solution is in the range of 1:1.5 to 1:2.5, and the amount of the first organic solution used is in the range of 900 to 1500 weight units, but more preferably, the amount of the first organic solution used is about 1200 weight units.

[0025] After the tungsten sulfide gel formation step S120 and before the heat treatment step S130, the glass fiber yarn manufacturing method further includes a washing and drying step S121, in which the tungsten compound gel is washed and filtered multiple times, and then the tungsten compound gel is calcined. Specifically, in the washing and drying step S121, the tungsten compound gel is washed using a washing liquid to remove unreacted impurities and remaining solutions (e.g., the first organic solution). The washing liquid is, for example, water, ethanol, isopropanol, etc., but the present invention is not limited thereto. Furthermore, in the washing and drying step, the temperature and time for calcining the tungsten compound gel are in the range of 80°C to 120°C and 1 hour to 10 hours, respectively, but the present invention is not limited thereto.

[0026] In the heat treatment step S130, the tungsten sulfide gel is maintained in an environment of 600°C to 1200°C for 4 to 6 hours to form tungsten sulfide powder. The temperature and time of the heat treatment step S130 affect the crystal structure and properties of the formed tungsten sulfide powder. Specifically, if the temperature is too low, the conversion rate of the formed tungsten sulfide will be low and the crystal orientation will be non-uniform. The temperature of the heat treatment step S130 needs to be within a certain range so that the crystal orientation of the formed tungsten sulfide powder is concentrated, the signal intensity of the crystal plane is strong, and the physical properties of the tungsten sulfide powder (improved lubricity and wear resistance) are good. The temperature of the heat treatment step S130 is particularly preferably in the range of 650°C to 900°C.

[0027] Moreover, if the heat treatment step S130 is performed for too long, the tungsten sulfide powder will be too hard and difficult to coat on the silicon dioxide carrier, whereas if the heat treatment step S130 is performed for too short a time, the tungsten sulfide formed will have too many impurities.

[0028] Furthermore, the heat treatment step S130 can be performed under an argon gas or nitrogen gas atmosphere. Here, the argon gas or nitrogen gas atmosphere refers to a pure argon environment. If the heat treatment step S130 is not performed under an argon gas or nitrogen gas atmosphere, the oxygen in the environment may oxidize the tungsten sulfide powder, thereby affecting the maximum static friction coefficient of the glass fiber yarn 100.

[0029] In the coating step S140, the tungsten sulfide powder is coated on the surfaces of the inorganic particles to form a plurality of surface-modified inorganic particles 1. The surface-modified inorganic particles 1 have a core-shell structure, which includes a core layer 11 formed from inorganic particles and a shell layer 12 formed from tungsten sulfide powder. With respect to a total weight of 100 wt% of all the surface-modified inorganic particles, the content of the tungsten sulfide powder ranges from 0.01 wt% to 5 wt%, and the content of the inorganic particles ranges from 95 wt% to 99.9 wt%. The particle diameter of each inorganic particle ranges from 0.01 μm to 50 μm.

[0030] Specifically, in the coating step S140, the tungsten sulfide powder is first dispersed in a second organic solution, and then the tungsten sulfide powder and the second organic solution are added to the inorganic particles, and the tungsten sulfide powder, the second organic solution, and the inorganic particles are stirred so that the tungsten sulfide powder is coated on the surfaces of the inorganic particles to form the surface-modified inorganic particles 1. More specifically, in the coating step S140, the tungsten sulfide powder is dispersed in the second organic solution rather than dissolved therein. The method of dispersing the tungsten sulfide powder in the second organic solution includes, for example, mechanical grinding and ultrasonic treatment, but the present invention is not limited thereto. The second organic solution containing the tungsten sulfide powder is added dropwise to the inorganic particles being stirred, and after further stirring, the tungsten sulfide powder, the second organic solution, and the inorganic particles are dried to obtain the surface-modified inorganic particles 1.

[0031] The second organic solution is, for example, isopropanol, and the inorganic particles are at least one selected from a group of materials consisting of silicon dioxide, titanium dioxide, aluminum hydroxide, magnesium hydroxide, calcium carbonate, aluminum oxide, and calcined kaolin, but the present invention is not limited thereto.

[0032] In the mixing step S150, a plurality of surface-modified inorganic particles 1 are mixed into the molten glass frit 2. With respect to the total weight of the glass frit being 100wt%, the glass frit 2 can contain, for example, 54wt% to 63wt% silicon oxide, 15wt% to 24wt% aluminum oxide, 6wt% to 13wt% magnesium oxide, 3.4wt% to 14wt% calcium oxide, 0.5wt% to 9wt% boron oxide, and 0wt% to 7wt% rhenium oxide, but the present invention is not limited to the specific components contained in the glass frit 2 and the content of each component.

[0033] In the spinning step S160, a plurality of glass fiber threads are formed by spinning a glass raw material 2 containing a plurality of surface-modified inorganic particles 1. With respect to a total weight of 100 wt% of each glass fiber thread 100, the content of the surface-modified inorganic particles 1 is in the range of 0.1 wt% to 5 wt%, and the content of the glass raw material 2 is in the range of 95 wt% to 99.9 wt%.

[0034] It is noteworthy that after the spinning step S160, the glass fiber yarns 100 have excellent slip properties, and therefore there is no need to further add a lubricant to the surface of the glass fiber yarns 100 after the spinning step S160. Moreover, in the present invention, the surface-modified inorganic particles 1 are not only on the surface of the glass fiber yarns 100 but are also uniformly dispersed therein, making the glass fiber yarns 100 less likely to break in the spinning step S160.

[0035] In other words, the glass fiber yarn manufacturing method in which the lubricant is added after the spinning step, or the glass fiber yarn in which the lubricant is present only on the surface, is not suitable compared to the glass fiber yarn manufacturing method of the present invention and the glass fiber yarn 100. Furthermore, when the lubricant is added only on the surface of the glass fiber yarn, the lubricity inside the glass fiber yarn is not improved, so that the glass fiber yarn easily breaks during the spinning process.

[0036] Furthermore, if the tungsten sulfide powder is directly added to the glass raw material 2, the tungsten sulfide powder will not be uniformly dispersed in the glass fiber yarn 100. Therefore, in the manufacturing method of the glass fiber yarn of the present invention, the tungsten sulfide powder is first coated on the surface of the inorganic particles to form the surface-modified inorganic particles 1, and then the surface-modified inorganic particles 1 are dispersed in the glass raw material 2, so that the surface-modified inorganic particles 1 are uniformly dispersed in the glass fiber yarn 100.

[0037] Each fiberglass yarn 100 has a maximum static friction coefficient in the range of 0.39 to 0.48. It is further noted that since the melting point of tungsten sulfide is in the range of approximately 1500° C. to 1550° C., the fiberglass yarn 100 containing the surface-modified inorganic particles 1 has excellent thermal stability.

[0038] [Glass fiber yarn] The present invention also provides a glass fiber yarn 100. The glass fiber yarn 100 is manufactured by the above-mentioned glass fiber yarn manufacturing method, but is not limited thereto. The glass fiber yarn 100 includes a glass frit 2 and a plurality of surface-modified inorganic particles 1 dispersed in the glass frit 2.

[0039] Each surface-modified inorganic particle includes inorganic particles and tungsten sulfide powder coated on the inorganic particles. The surface-modified inorganic particles 1 have a core-shell structure, which includes a core layer 11 formed by inorganic particles and a shell layer 12 formed by tungsten sulfide powder. The content of the tungsten sulfide powder ranges from 0.01 wt% to 5 wt% with respect to the total weight of all the surface-modified inorganic particles being 100 wt%. The inorganic particles are at least one selected from a group of materials consisting of silicon dioxide, titanium dioxide, aluminum hydroxide, magnesium hydroxide, calcium carbonate, aluminum oxide, calcined kaolin, etc.

[0040] The particle size of each inorganic particle ranges from 0.01 μm to 50 μm. The content of the surface-modified inorganic particles ranges from 0.1 wt% to 5 wt% relative to the total weight of all the glass fiber yarns (100 wt%).

[0041] The fiberglass yarn has a maximum static coefficient of friction ranging from 0.39 to 0.48.

[0042] [Experimental Data Test] The present invention will be described in detail below with reference to Examples 1 to 3 and Comparative Example 1. However, the following examples are provided to help understand the present invention, and the scope of the present invention is not limited to these examples.

[0043] No surface-modified inorganic particles were added in Comparative Example 1. In the glass fiber yarn manufacturing methods of Examples 1 to 3, the contents of the surface-modified inorganic particles were 0.2 wt%, 1 wt%, and 2 wt%, respectively, relative to 100 wt% of the total weight of the glass fiber yarn.

[0044] The data on the maximum static friction coefficient, abrasion resistance, thermal stability and electrical conductivity of the glass fiber yarns produced by Comparative Example 1 and Examples 1 to 3 are listed in Table 1 below, and the related test methods are as follows:

[0045] Testing maximum static friction coefficient: Take two samples of 5 millimeter thickness composed of glass fiber yarn, and use a friction coefficient tester model number CFT-400 to test the maximum static friction coefficient of the samples under a load condition of 200 grams.

[0046] Abrasion Resistance Test: A sample made from glass fiber yarn is brought into contact with the grinding wheel of a grinder, and the abrasion resistance of the sample is observed and evaluated.

[0047] Thermal stability test: Use a thermomechanical analyzer to test the thermal expansion coefficient of samples made from fiberglass yarn.

[0048] [Table 1]

[0049] [About the test results] The more surface-modified inorganic particles are added, the lower the maximum static friction coefficient becomes, and the more wear resistance improves, allowing the structural integrity and appearance quality of the product to be maintained for a long time and the product's service life to be extended. In high-friction environments, the wear resistance of glass cloth made from glass fiber yarn reduces heat generation due to friction, preventing excessive temperature rise and material damage, and contributing to protecting the safety of equipment and structures.

[0050] The data on the coefficient of thermal expansion shows that the more the surface-modified inorganic particles are added, the more the heat resistance improves. Glass cloth with strong heat resistance maintains structural stability even at high temperatures and is less likely to melt or deform. This is very important for applications that require maintaining shape and strength in high-temperature environments, such as fire isolation materials and high-temperature screening processes. Therefore, the surface-modified inorganic particles provided in the present invention can improve the physical properties of glass fiber yarn.

[0051] [Beneficial Effects of the Embodiments] One beneficial effect of the present invention is that the glass fiber yarn and the manufacturing method thereof provided by the present invention can effectively solve the problem that the existing glass fiber yarn easily breaks during the spinning process through the technical solution of "a tungsten compound gel forming step, a tungsten sulfide gel forming step, a heat treatment step, a coating step, a mixing step and a spinning step" and "a plurality of surface-modified inorganic particles are dispersed in the glass raw material".

[0052] The above disclosure is merely a preferred embodiment of the present invention, and does not limit the scope of the claims of the present invention. Therefore, all equivalent technical modifications made based on the contents of the specification and accompanying drawings of the present invention shall be included in the scope of the claims of the present invention. [Explanation of symbols]

[0053] 100 Glass Fiber Yarn 1. Surface-modified inorganic particles 11 Core layer 12 Shell Layer S110 Tungsten compound gel formation step S120 Tungsten sulfide gel formation step S121 Washing and drying step S130 Heat treatment step S140 Coating Step S150 Mixing Step S160 Spinning Step

Claims

1. a tungsten compound gel forming step of dissolving a tungsten compound in a first organic solution to form a tungsten compound gel; a tungsten sulfide gel forming step of adding a sulfur source to the tungsten compound gel and stirring the sulfur source and the tungsten compound gel to form a tungsten sulfide gel; a heat treatment step of maintaining the tungsten sulfide gel in an environment of 600° C. to 1200° C. for 4 to 6 hours to form tungsten sulfide powder; A step of coating the tungsten sulfide powder on the surface of a plurality of inorganic particles to form surface-modified inorganic particles, wherein the content of the tungsten sulfide powder is in the range of 0.01 wt % to 5 wt % relative to the total weight of the surface-modified inorganic particles being 100 wt %; A mixing step of mixing a plurality of the surface-modified inorganic particles into a molten glass raw material; a spinning step of spinning the glass frit containing a plurality of the modified inorganic particles to form a glass fiber yarn; Includes A method for producing glass fiber yarn.

2. 2. The method for producing glass fiber yarn according to claim 1, further comprising a washing and drying step after the tungsten sulfide gel forming step and before the heat treatment step, wherein the washing and drying step includes washing and filtering the tungsten compound gel multiple times, and then drying the tungsten compound gel.

3. 2. The method for producing glass fiber yarn according to claim 1, wherein in the coating step, the tungsten sulfide powder is first dispersed in a second organic solution, and then the tungsten sulfide powder and the second organic solution are added to the inorganic particles, and then the tungsten sulfide powder, the second organic solution and the inorganic particles are stirred to coat the inorganic particles with the tungsten sulfide powder, thereby forming the surface-modified inorganic particles.

4. 2. The method of claim 1, wherein the tungsten compound is tungsten hexachloride.

5. 2. The method of claim 1, wherein the weight ratio of said tungsten compound to said sulfur source ranges from 5:1 to 8:

1.

6. 2. The method of claim 1, wherein the inorganic particles are at least one of the group of materials consisting of silicon dioxide, titanium dioxide, aluminum hydroxide, magnesium hydroxide, calcium carbonate, aluminum oxide, and calcined kaolin.

7. The method for producing glass fiber yarn according to claim 1, wherein the particle diameter of the inorganic particles is in the range of 0.01 μm to 50 μm.

8. 2. The method for producing glass fiber yarn according to claim 1, wherein the content of the surface-modified inorganic particles is in the range of 0.1 wt % to 5 wt % relative to 100 wt % of the total weight of the glass fiber yarn.

9. 2. The method of claim 1, wherein each of said fiberglass yarns has a maximum static coefficient of friction in the range of 0.39 to 0.

48.

10. A glass fiber yarn comprising a glass frit and a plurality of surface-modified inorganic particles dispersed in the glass frit, The surface-modified inorganic particles include inorganic particles and tungsten sulfide powder coated on the inorganic particles, Based on the total weight of the surface-modified inorganic particles being 100 wt%, the content of the tungsten sulfide powder is in the range of 0.01 wt% to 5 wt%; The inorganic particles are at least one of the group of materials consisting of silicon dioxide, titanium dioxide, aluminum hydroxide, magnesium hydroxide, calcium carbonate, aluminum oxide, and calcined kaolin; A glass fiber yarn characterized by:

11. 11. The glass fiber yarn according to claim 10, wherein the particle size of the inorganic particles is in the range of 0.01 μm to 50 μm, and the content of the surface-modified inorganic particles is in the range of 0.1 wt % to 5 wt %, based on 100 wt % of the total weight of the glass fiber yarn.

12. 11. The fiberglass yarn of claim 10, wherein the maximum static friction coefficient of the fiberglass yarn is in the range of 0.39 to 0.48.

Citation Information

Patent Citations

  • JP1975010380A

  • Strand fiber for bundled fiber

    JP1984188604A

  • Fiber product coated with particles for adjusting friction of coating and inter-filament bonding

    JP2011219912A